Expert knowledge, ambidexterity, and is in Automotive Industry Engineering Projects (AIEP): Overview of a post clinical research - Azan, Wilfrid; Rolland, Olivier; Ivanaj, Silvester (Management international / International Management / Gestiòn Internacional, 2025)
This paper introduces a new form of ambidexterity in IS projects, drawing from the falsification of a clinical research conducted in an automotive engineering company, focusing on process reengineering and ERP implementation. It bridges clinical research (1997‑2001) with expert insights (2002‑2021). Addressing a gap in IS project literature, particularly within Automotive Industry Engineering Projects (AIEP), the study highlights that exploration-exploitation strategies may become dysfunctional in turbulent, cyclical environments. The article criticizes the short-sighted results of ERP strategies applied to simple automotive projects, and encourages better dialogue between practitioners and decision-makers, with a view to resourcing the IS in line with business cycles.